Retrospective real-world pilot data on transcranial pulse stimulation in mild to severe Alzheimer's patients - Cont, Celine; Stute, Nathalie; Galli, Anastasia; Schulte, Christina; Logmin, Kazimierz; Trenado, Carlos; Wojtecki, Lars (Frontiers in Neurology, 2022)
Introduction Transcranial pulse stimulation (TPS) is a non-invasive neuromodulation therapy that uses short, repetitive shockwaves through a neuro-navigated device. Current research suggests that these pulses lead to a wide range of vascular, metabolic, and neurotrophic changes. This relatively new CE-marked treatment provided first promising results in a clinical pilot study for improving cognition in mild-to-moderate Alzheimer's. Data from other centers is lacking, so here we analyzed safety and pilot real-world short-term results of TPS from the first center in Germany. To gain information about effects in different stages, patients with not only mild but also moderate-to-severe Alzheimer's were analyzed. Methods A total of 11 patients were retrospectively examined for cognitive and emotional function before and after the first stimulation series. The effect was assessed using several neuropsychological tests [Alzheimer's Disease Assessment Scale (ADAS), including the ADAS cognitive score (ADAS Cog) and ADAS affective scores, Mini-Mental Status Examination (MMSE), and Montreal Cognitive Assessment (MoCA)] including in comparison between the groups of mild-to-severe patients. Moreover, subjective improvement of symptom severity, potential effects on depressive symptoms, and side effects were analyzed using Numeric Rating Scales (NRS). Results Side effects were rare (in 4% of sessions) with moderate subjective severity and only transient. Patients significantly improved in the ADAS and ADAS Cog, while there was no significant effect in MMSE and MoCA. Patients' self-reported symptom severity improved significantly. The depressive symptoms measured in an ADAS subscale also improved significantly. Statistical data analyses revealed no significant correlation of clinical improvement with baseline symptom severity. Conclusion TPS might be a safe and promising add-on therapy for Alzheimer's, even for moderate-to-severe patients. More research on long-term effects in patients as well as studies with sham control groups is needed. Moreover, translational research on the mechanisms of action and effects on cerebral network physiology will be needed to understand this new neuromodulation technique.